2022
DOI: 10.1071/wf22029
|View full text |Cite
|
Sign up to set email alerts
|

Suppression resources and their influence on containment of forest fires in Victoria

Abstract: Background Wildfire suppression is becoming more costly and dangerous as the scale and severity of impacts from fires increase under climate change. Aims We aim to identify the key environmental and management variables influencing containment probability for forest fires in Victoria and determine how these change over time. Methods We developed Random Forest models to identify variables driving fire containment within the first 24 h of response. We used a database of ~12 000 incident records col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…They proposed a method to identify and detect grassland forest fire smoke by identifying carbon concentration, thereby improving sensor detection accuracy while reducing fire hazards [12]. In view of the high hazard of grassland forest fires, Marshall E and others proposed corresponding identification and detection methods based on the construction of a Random forest model, which effectively improved the probability of curbing grassland forest fires while reducing the actual response time [13]. Cardíl A et al proposed a new innovative method to address the issue of rapid spread of forest and grassland fire activities by clustering relevant hotspots such as visible infrared imaging into fire perimeter timelines, thereby effectively alleviating the actual harm of fires [14].Zhang L et al proposed a multi-scale fusion pyramid network and a fast robust network for early detection of forest fire smoke, which effectively improved detection accuracy [15].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They proposed a method to identify and detect grassland forest fire smoke by identifying carbon concentration, thereby improving sensor detection accuracy while reducing fire hazards [12]. In view of the high hazard of grassland forest fires, Marshall E and others proposed corresponding identification and detection methods based on the construction of a Random forest model, which effectively improved the probability of curbing grassland forest fires while reducing the actual response time [13]. Cardíl A et al proposed a new innovative method to address the issue of rapid spread of forest and grassland fire activities by clustering relevant hotspots such as visible infrared imaging into fire perimeter timelines, thereby effectively alleviating the actual harm of fires [14].Zhang L et al proposed a multi-scale fusion pyramid network and a fast robust network for early detection of forest fire smoke, which effectively improved detection accuracy [15].…”
Section: Related Workmentioning
confidence: 99%
“…In formula (12), xy ψ represents the Central moment of order x y + ; ( ) 0 0 , p q represents the actual centroid coordinates of the target area, and its calculation expression is shown in formula ( 13) and ( 14). In formula (13), 0 p represents the abscissa of the center of mass; 10 l represents the first order origin moment; 00 l represents the zero order origin moment. In formula ( 14), 0 q represents the centroid ordinate; 01 l also represents the first order origin moment.…”
Section: ( )( ) ( )mentioning
confidence: 99%
“…Predicting the risk of these fires is typically done with fire danger or behaviour indices which can distinguish between days of high potential. Recent work has focused on modelling the probability of initial attack (IA) success (Plucinski 2012;Collins et al 2018;Marshall et al 2022) by different definitions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main challenges with these models is that their supporting data can be severely zero-inflated as most IA is successful. Some research has found that response data, such as the number of firefighting resources deployed, is a key predictor of initial attack being unsuccessful (Collins et al 2018;Marshall et al 2022). This highlights the importance of resource allocation and effective management in responding to wildfires.…”
Section: Introductionmentioning
confidence: 99%